An Experimental Investigation into the Ignition and Combustion Characteristics of Single Droplets of Biochar Slurry Fuels. (August 2015) - Zhu, Mingming; Zhang, Zhezi; Chan, Yii Leng; Yani, Setyawati; Zhang, Dongke
Abstract: The ignition and combustion behaviour of single droplets of slurry fuels made from a coconut shell biochar was experimentally investigated.The slurry fuels were prepared with water content varying from 50 to 70wt% and the median particle size (D50 ) of the biochar of approximately 10 μm. The suspended single droplets of the slurry fuels wereignited and burned in air at 1023K. The ignition delay time, burnout time and burning ratewere measured. It was found that the ignition delay time slightly increased as the water content increased from 50wt% to 65wt% but then decreased as the water further increased to 70wt%, indicating that the effect of water content on the ignition delay time is a trade-off between the water evaporation time and biochar oxidation rate. Increasing droplet size or decreasing water content led to longer burnout timesof residual biochar. The burning rate of the residual biochar decreased with increasing the droplet size or decreasing water content.